Late neointimal volume reduction is observed following biodegradable polymer-based drug eluting stent in porcine model. (June 2021) - Ijichi, Takeshi; Nakazawa, Gaku; Torii, Sho; Nagamatsu, Hirofumi; Yoshikawa, Ayako; Nakamura, Shintaro; Souba, Junko; Isobe, Atsushi; Hagiwara, Hitomi; Ikari, Yuji
Abstract: Background: The BP-SES has an abluminally applied biodegradable polymer that is fully resorbed after 3–4 months but may have longer-lasting effects. The aim of this study was to determine the long-term vascular response to the novel Ultimaster™ sirolimus-eluting stent (BP-SES). Methods: BP-SESs, everolimus-eluting stents (DP-EESs), and bare metal stents were implanted in 22 coronary arteries of 15 mini-swine. All animals underwent optical frequent domain imaging (OFDI) to assess neointimal volume and quality at either 1 (n = 7) or 3 (n = 8) months and at 9 (n = 15) months and were euthanized at 9 months. Stents were subsequently histologically investigated to analyze the vascular response and maturity of neointimal tissue according to cell density. Results: OFDI revealed greater regression in neointimal volume from 3 to 9 months with BP-SESs than with DP-EESs (−0.6 ± 0.5 mm 2 vs. 0.00 ± 0.4 mm 2, p  = 0.07). Although there was no significant difference between BP-SESs and DP-EESs in the inflammation score (BMS, BP-SES, and DP-EES: 0.1 ± 0.1, 0.3 ± 0.4, and 0.4 ± 0.4, respectively; p  < 0.0001) in histological analysis, BP-SESs showed slightly greater maturity than DP-EESs (1.8 ± 0.3, 1.7 ± 0.3, and 1.6 ± 0.3, p  = 0.09). Conclusions: While both BP-SESs and DP-EESs showed minimal inflammatory responses at 9 months, BP-SESs showed a trend for greater neointimal maturity and regression, which may be related to earlier completion of the vascular response.